Correlation between Students’s Ability to Memorize the Qur’an and Students’ Learning Achievement at Islamic Boarding Schools in Indonesia - Novebri, Novebri; Dewi, Sinta (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2020)
This study aims to investigate the correlation between students’ ability to memorize the Qur’an and students’ learning achievement in the subject of al-Quran and hadiths. To achieve the objective, the study utilized quantitative method under the frame of correlational design involving seventy eleventh grade students who took al-Qur’an hadiths subject. To collect the data, the study utilized questionnaires. The obtain data were then analyzed by using correlation analysis technique through SPPS 20.0 software. The results showed that the ability to memorize the Qur'an has a significant correlation with the students’ learning achievement in the subject of al-Qur'an hadith. It is evidenced in the results of analysis that the two variables were correlated around 52.3% with a determination coefficient of 0.523 and a significance level (ρ) of 0.000. The students who have the ability to memorize the Qur’an have strong memories, good attention to details and brilliant thoughts because the students may have a lot of practice in matching the verses in the Qur’an with their memorization or recitation,. Therefore, it is expected that by increasing their ability in memorizing the Qur’an, the students can improve their learning achievement in the subject of al-Qur'an hadith since it uses Arabic as the Qur'an does.